Measuring the outcomes of medial meniscectomies with a femoral end medial collateral ligament release and reattachment in patients with a tight knee: a case series - Parhar, Kanwar; Frolov, David; Tapio, Ryan; Slack, Katherine; Schmitz, Miguel A. (International Journal of Research in Orthopaedics, 2024)
Partial meniscectomies are the most commonly performed arthroscopic knee procedures, however, are complicated by the presence of a tear in the posterior medial compartment (PMC) in tandem with a “tight knee”. This inhibits adequate spacing for instrumentation access, increasing the chances of causing iatrogenic cartilage damage which can progress to early onset osteoarthritis. We present a unique method for increasing the joint space, in such cases, and avoiding cartilage damage, by performing a femoral end medial collateral ligament release and reattachment (MCLR). Patient outcomes were evaluated in two parts. The first part compared the fourteen patients who underwent a MCLR pre- and post-operatively via the Lysholm and Tegner score, VAS pain scale and knee flexion angle. Finally, the MCLR patients were compared via 1:1 propensity score-matching to patients who underwent a valgus maneuver only for a PMC tear. The patients receiving an MCLR showed a statistically significant improvement (p<0.001) within each of the pre- and post-operative measured variables. When compared with 1:1 propensity score matched and unmatched patients, no statistically significant difference was seen between the Lysholm, Tegner and Flexion angle while VAS pain scale did show a difference. For patients requiring a PMM with a “tight knee”, performing an MCLR provides a clinical and functional improvement in symptoms and showed no statistically significant difference when compared with valgus maneuver only patients. Therefore, it is an effective procedure for increasing the joint space in a patient with a tight knee that requires a partial medial meniscectomy (PMM).